EVIDENCE : Bhartiya Sakshya Adhiniyam - Sharma, Ved Bhushan (New Delhi D.P.S. Publishing, 2025)
CONTENTS: 1. Significant changes in Bharatiya Sakshya Adhiniyam 2. Significance of digital evidence in criminal investigations 3. Here are some of the key changes introduced in the Bharatiya Sakshya Adhiniyam 4. Importance of preserving scientific evidence in criminal investigation 5. How weak evidence can destroy criminal investigation during trials? 6. Whether the conviction rate will be higher under the Bharatiya Sakshya Adhiniyam (BSA) 7. The crucial role of clinching evidence in criminal trials 8. Preservation of evidence by prosecuting agencies 9. Effective production of evidence in court for a successful conviction 10. Factors Contributing to a Successful Criminal Prosecution 11. Short guidelines for action to be taken in different situation 12. Salient/Social features in Bharatiya Sakshya Adhiniyam 13. Murder case 14. Attempt to Murder Case 15. Accidental Death 16. Dowry Death 17. Attempt to commit culpable homicide 18. Voluntarily causing Hurt by dangerous weapon 19. Voluntarily causing Grievous hurt by dangerous weapon 20. Causing hurt by means of poison etc with Intent to commit an offence 21. Rape and Posco Acts 22. Mob Lynching case 23. House breaking 24. Kidnapping Case 25. Kidnapping (for ransom) case 26. Snatching 27. Riot case 28. Attempt to commit Robbery when armed with deadly weapon 29. Abetment of suicide 30. Negligent conduct with respect to explosive substances 31. Obscene acts and songs 32. Word gesture or act intended to insult modesty of a woman 33. Voluntarily causing grievous hurt 34. Act endangering life or personal safety of other 35. Wrongful restraint 36. Assault or criminal force to deter public servant from discharge of his duty 37. Assault or use of criminal force to woman with intent to outrage her modesty 38. Sexual harassmen 39. Assault or use of criminal force to woman with intent to disrobe 40. Voyeurism 41. Stalking 42. Criminal trespass and house trespass 43. Robbery 44. Stolen property 45. Cheating 46. Criminal trespass and house trespass 47. Marrying again during lifetime of husband or wife 48. Husband or relative of husband of a woman subjective her to cruelty 49. Criminal intimidation 50. Suggested guidelines for establishing evidence response teams 51. Digital Arrest 52. Insurance Fraud/Cheating
Keywords: Law; Bharatiya Sakshya Adhiniyam: Evidence